A rare case report of 32 years old female suffering from lupus panniculitis as an initial sign of systemic lupus erythematosus - Shaheen, Shaikha Abdulla; Barrouq, Deena M. Shaker (International Journal of Research in Medical Sciences, 2023)
This case report describes a rare case of lupus panniculitis (LEP) in a 32-year-old Egyptian lady who did not have any history of chronic illness. The patient initially presented with leg pain, erythematous nodules, and back ulcers. In addition to proteinuria and increased erythrocyte sedimentation rate (ESR) levels, laboratory tests revealed atypical ANA titers and positive results for anti-DNA, anti-Scl 70, anti-SSa, and anti-SSb antibodies. There was a decline in C3 and C4 levels. A physical examination revealed well-defined ulcers on her back and subcutaneous lumps in both of her legs. The diagnosis of LEP was confirmed by a nodule biopsy. Systemic lupus erythematosus (SLE) was finally determined to be the patient’s diagnosis in accordance with the classification standards of the American College of Rheumatology. Methylprednisolone therapy resulted in the resolution of ulcers and nodules, as well as normalization of CBC and C3 levels and a drop in ANA titer. In order to enhance patient outcomes, this example highlights the necessity of treating LEP as a symptom of SLE and the value of early diagnosis and treatment.